Evaluación de las decisiones financieras operacionales que generan flujo de caja en las MIPYMES; Evaluation of operational financial decisions that generate cash flow in Msmes - Agustin María Martínez Vargas; Marcos Edilson Hernández; Omar Velásquez Cerón (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– The objective of the research is to identify the variables that affect short-term financial decisions, determinants of cash flow in MSMEs. A mixed investigation is carried out, based on a survey applied to 278 managers of Micro, Small and Medium Enterprises (MSMEs) in Colombia. The data were analysis based on binary logistic regression and information was managed through executions, oriented to the management of multipurpose events, where training, informal discussion as a focus group and observation of participants' reactions to intentionality and significance of the project are the essence. The results show that financial decisions in the MSMEs are headed by the directors who should wield their leadership, experience, knowledge and skills in financial and strategic training to make decisions aimed at optimizing cash flow even without training. optimal required. A circumstance that to a large extent, especially in micro, small and medium sized companies, new in the market, leads them to finance their activity with their own resources, family resources or informal credit while very few opt for external financing. Operational financial decisions become a complex, empirical, carefree and improvised process for many MSMEs, this being an attenuating factor of the lack of sustainability in the market and in a wide margin of failure.
Keywords: C53; D21; G11; M21; 330; financial management; liquidity; solvency; working capital; binary logisticregression